Developing the sensor system for lower limb rehabilitation robot : for shifting of body-weight via insole flexi-force sensing - Low, Mui Yen. (2009)
This report reflects the methods for device-assisted body-weight shifting (BWS) during walking rehabilitation. The relevance of this report to device-assisted BWS is that it presents the specific kinematics of pelvis during walking, and suggests a way in which modification of the current robotic rehabilitation robot to assist patient with body-weight shifting can be implemented. The value of this report in relation to the study of lower-limb rehabilitation is the intensive literature study and the record of relevant experiments that involve some of the clinical rehabilitation equipment, in particular the electromyography system and the piezoelectric sensors.